2016
DOI: 10.1111/petr.12720
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives for vascular reconstruction in pediatric living donor liver transplantation

Abstract: Many publications discuss the various strategies for vascular reconstruction (VR) in pediatric LDLT. Having knowledge of alternative techniques is helpful in planning transplants. This article presents three case reports that illustrate some of the alternative techniques for HV, PV, and HA reconstruction in pediatric LDLT. It also reviews the available alternative strategies reported for VR in pediatric LDLT. In the first case, a 13-month-old girl presented a PRETEXT III HB with invasion of the retrohepatic ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Caval replacement would have been the best procedure for the patient of the present case if a deceased donor graft had been available. Caval replacement using a vascular graft, such as a cryopreserved or synthetic graft, may be an alternative in the setting of LDLT; however, there is a certain risk of thrombus and infection with the use of any type of vascular graft . Moreover, the long‐term patency of vascular grafts is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caval replacement would have been the best procedure for the patient of the present case if a deceased donor graft had been available. Caval replacement using a vascular graft, such as a cryopreserved or synthetic graft, may be an alternative in the setting of LDLT; however, there is a certain risk of thrombus and infection with the use of any type of vascular graft . Moreover, the long‐term patency of vascular grafts is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Caval replacement using a vascular graft, such as a cryopreserved or synthetic graft, may be an alternative in the setting of LDLT; however, there is a certain risk of thrombus and infection with the use of any type of vascular graft. 7,8 Moreover, the long-term patency of vascular grafts is still unknown. Wang et al reported on outflow reconstruction of the right anterior sector in a right liver graft with a cryopreserved vascular graft and noted that the patency rates at 2 weeks and 2 years after LDLT were 90%-94% and 54.5%-61.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Two recipients were much older than our patient, and either an extended left lobe graft or a left lobe graft was used in those patients [ 2 , 7 ]. One recipient received a left lateral lobe graft, but he was much older than our patient [ 8 ]. To our knowledge, our patient was the youngest case of RPA in pediatric LDLT with a left lateral lobe graft.…”
Section: Discussionmentioning
confidence: 99%